Effects of pregnancy-specific β-1-glycoprotein on the helper T-cell response - Timganova, Valeria; Bochkova, Maria; Khramtsov, Pavel; Kochurova, Sofia; Rayev, Mikhail; Zamorina, Svetlana (Archives of Biological Sciences, 2019)
Paper description: Pregnancy-specific β-1-glycoproteins (PSGs) are capable of regulating innate and adaptive immunity. As fetal antigens circulate in pregnant women blood, it is of particular interest to reveal the effects of PSGs on memory T cell differentiation in the context of maternal-fetal tolerance development. We found that PSG reduces the frequencies of CD4+CD45RA+ effector memory (TEMRA) and CD45RA+CD45R0+ T-cells, while inhibiting IL-4 and IFN-γ production by total helper T-cells in vitro. As TEMRA-cells exhibit cytotoxic activity that is unfavorable during pregnancy, the revealed PSG effects might play a fetoprotective role in vivo. Abstract: Pregnancy-specific β-1-glycoproteins (PSGs) are capable of regulating innate and adaptive immunity. As fetal antigens circulate in the blood of pregnant women, it is of particular interest to reveal the effects of PSGs on the differentiation of memory T cells in the context of maternal-fetal tolerance formation. We studied if, native PSG preparation affects helper T-cell proliferation, the frequencies of CD4+CD45R0+, CD4+CD45RA+, CD4+CD45RA+CD45R0+cells, naive CD45RA+CD45R0-CD62L+ cells (NAIVE), central memory CD45RA-CD45R0+CD62L+ cells (TCM) and effector memory helper T cells (CD45RA-CD45R0+CD62L- (TEM) and CD45RA+CD45R0-CD62L- cells (TEMRA), together with IL-4 and IFN-γ production by all СD4+ T cells. The suppressive effect of PSG on helper T-cell proliferation was established. It was found that PSG does not influence the frequencies of CD45RA+ and CD45R0+ cells, while it decreased the percentage of CD45RA+CD45R0+ cells. PSG increased the percentage of NAIVE cells in culture, and prevented the conversion of these cells into TEMRA, without affecting the levels of TCM and TEM. In addition, PSG lowered the amount of IL-4 and IFN-γ in the supernatants of helper T-cell cultures. As TEMRA exhibit cytotoxic activity that is unfavorable during pregnancy, the revealed PSG effects may play a fetoprotective role in vivo. https://doi.org/10.2298/ABS190122019T Received: January 22, 2019; Revised: March 15, 2019; Accepted: March 21, 2019; Published online: March 25, 2019 How to cite this article: Timganova V, Bochkova M, Khramtsov P, Kochurova S, Rayev M, Zamorina S. Effects of pregnancy-specific β-1-glycoprotein on the helper T-cell response. Arch Biol Sci. 2019;71(2):369-78.